Student evaluations of teaching do not reflect student learning: an observational study - Gilbert, R. O.; Gilbert, D. R. (BMC medical education, 2025)
Background Student Evaluations of Teaching (SET), of individual instructors and of courses, are routinely utilized by university administrators for consequential decisions regarding individual faculty members, courses, and curricula. Despite their ubiquity, much evidence exists that they are biased, amongst other factors by expected and received student grades. To our knowledge, this issue has not been examined in veterinary education until recently. Furthermore, it remains unclear whether observed combinations of higher grades and more favorable student evaluations using common survey instruments reflect enhanced learning. Our study evaluates the relationship between (A) student evaluations of courses in a veterinary curriculum, (B) grades earned in those courses, and (C) an independent measure of learning in those subjects. Methods The Veterinary Educational Assessment (VEA) is an independent, external examination in basic sciences subjects prepared by the National Board of Medical Examiners and administered by the International Council for Veterinary Assessment and is taken by Ross University School of Veterinary Medicine (RUSVM) students in their fifth semester of study. It offers an external means of measuring student learning in specific subjects and relating them to course evaluations. RUSVM has three terms each year with three separate intakes of students. Course evaluations and student grades were recorded for courses from fall 2018 to summer 2022, spanning 12 cohorts of students, and 160 individual courses. Courses were aligned to the relevant section of the VEA taken by each cohort. Spearman correlation coefficients were calculated. Results Mean course evaluations were significantly positively correlated to median grade in the course ( rho = 0.35, P < 0.0001) and the proportion of students earning A-grades ( rho = 0.38, P < 0.0001). The relationship between course evaluation and relevant VEA score was negative ( rho = -0.18, P = 0.02), indicating that students judged courses favorably when higher grades were expected without necessarily learning more from those courses. Conclusions We confirmed the well-known relationship between SET and student grades but, for the first time in veterinary medicine, describe a small but negative and statistically significant relationship between SET and an independent measure of learning. SET should be interpreted with caution; their use for evaluation of teachers or courses may have unintended consequences including reduced expectations for student achievement.